2021
DOI: 10.3390/ijerph182312644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training on Inflammatory Biomarkers in Patients with Type 2 Diabetes. A Systematic Review

Abstract: Background: Due to the prevalence and incidence worldwide of type 2 diabetes, and the significant role physical activity plays in these patients, a systematic review has been conducted to find out the effects that high-intensity interval training has on inflammatory biomarkers in subjects with type 2 diabetes. This project aims to determine the effect this training modality has on inflammatory biomarkers, in addition to observing its effects on the values of body composition and determining if this is a more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Several meta-analyses have already revealed the potential of HIIT to reduce markers of inflammation in various populations, including healthy individuals [ 81 , 82 ], overweight and obese cohorts [ 44 ], and patients with cardiometabolic disorders [ 81 , 82 , 83 , 84 ]. However, currently, data on the effects of low-volume HIIT (i.e., protocols with a maximal session duration of ≤30 min and ≤10 min of intense exercise, respectively, as previously defined [ 28 ]) are still very sparse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several meta-analyses have already revealed the potential of HIIT to reduce markers of inflammation in various populations, including healthy individuals [ 81 , 82 ], overweight and obese cohorts [ 44 ], and patients with cardiometabolic disorders [ 81 , 82 , 83 , 84 ]. However, currently, data on the effects of low-volume HIIT (i.e., protocols with a maximal session duration of ≤30 min and ≤10 min of intense exercise, respectively, as previously defined [ 28 ]) are still very sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Given that “lack of time” is a major obstacle to regular exercise for obese individuals [ 26 ], it is a key result of our investigation that engaging in less than 30 min of exercise per week is still effective to induce significant improvements in inflammation status and cardiometabolic indices in obese patients with MetS, which may be an important factor to enable greater adherence to exercise regimes over time. Although data suggest that higher-intensity exercise may also be more effective in reducing CRP levels compared to lower-intensity exercises [ 87 ], recent meta-analyses did not provide clear evidence whether HIIT is generally superior to traditional MICT regarding the effects on inflammation status [ 82 , 84 ]. We speculate therefore, that both modalities may provide similar benefits in this respect, with HIIT, however, requiring less time compared to MICT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that regular HIIT bouts can lead to better cardiovascular health through increased VO 2max and improved muscle metabolism (13,14). Moreover, studies in metabolic disorders show that HIIT has a positive effect on systemic in ammatory markers linked to the disease state (15,16). The signi cance of HIIT for disease development in rheumatic disorders in general, including the response in levels of in ammatory markers, have not been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and sedentary lifestyle have been associated with obesity [ 12 ], lean mass [ 13 ], glycemic status [ 14 ], and inflammation [ 15 ], which are vital factors for the development of T2DM. Nevertheless, whether and how these factors mediate the associations of physical activity and sedentary behaviors with diabetes risk are unestablished.…”
mentioning
confidence: 99%